21st Century Skills: A Proposal for ELT Teachers Successful Performance Today - López Prieto, Adriana (Coloquio, 2023)
This article addresses a reflective study on 21st century ELT teachers’ necessary skills atschool level in Colombia. The study aimed to analyze a set of abilities that enable teachers toperform successfully in a contemporary classroom setting by understanding the pivotal roleof ICTs, adaptability, and communicative-social skills to guarantee the accomplishment ofstudents’ expected learning outcomes. Data were collected through documentary analysis ofacademic research articles. Findings revealed that mastering 21st century teaching skillsequips ELT educators with the required knowledge to provide students with a rewardinglearning experience. As a conclusion, the integrative employment of a particular array ofskills aligned with present-day educational standards cultivates highly proficient teacherswho are capable of effectively navigating both their teaching context and that of theirstudents.